Retrosynthesis of CaCO3 via amorphous precursor particles using gastroliths of the Red Claw lobster (Cherax quadricarinatus) - Neira-Carrillo, A.; Fernández, M.; Hevia, G.; Arias, J.; Gebauer, Denis; Cölfen, H. (2017)
Â© 2017 Elsevier Inc. Gastroliths are highly calcified structures formed in the cardiac stomach wall of crustaceans for the temporary storage of amorphous CaCO 3 (ACC). The gastrolithic ACC is stabilized by the presence of biomolecules, and represents a novel model for research into biomineralization. For the first time, an in vitro biomimetic retrosynthesis of scaffolds of gastrolithic matrices with CaCO 3 is presented. With the help of synthetic polyacrylic (PAA) and phytic (PA) acids, amorphous precursor particles were stabilized in double (DD) and gas (GD) diffusion crystallization assays. The presence of these synthetic molecules as efficient inhibitors of nucleation and growth of CaCO 3 , and the use of biological gastrolith scaffolds as confined reaction environments determined the kinetics of crystallization, and controlled the morphogenesis of CaCO 3 . The formation of ACC particles was demonstrated and their crystallization was followed by light microscopy, scanning and transmission electron microscopy, and electron diffraction.